Chromosome-scale genome assembly of Cucumis hystrix—a wild species interspecifically cross-compatible with cultivated cucumber. (1st March 2021) - Qin, Xiaodong; Zhang, Zhonghua; Lou, Qunfeng; Xia, Lei; Li, Ji; Li, Mengxue; Zhou, Junguo; Zhao, Xiaokun; Xu, Yuanchao; Li, Qing; Yang, Shuqiong; Yu, Xiaqing; et al.
Abstract: Cucumis hystrix Chakr. (2n = 2x = 24) is a wild species that can hybridize with cultivated cucumber ( C. sativus L., 2n = 2x = 14), a globally important vegetable crop. However, cucumber breeding is hindered by its narrow genetic base. Therefore, introgression from C. hystrix has been anticipated to bring a breakthrough in cucumber improvement. Here, we report the chromosome-scale assembly of C. hystrix genome (289 Mb). Scaffold N50 reached 14.1 Mb. Over 90% of the sequences were anchored onto 12 chromosomes. A total of 23, 864 genes were annotated using a hybrid method. Further, we conducted a comprehensive comparative genomic analysis of cucumber, C. hystrix, and melon ( C. melo L., 2n = 2x = 24). Whole-genome comparisons revealed that C. hystrix is phylogenetically closer to cucumber than to melon, providing a molecular basis for the success of its hybridization with cucumber. Moreover, expanded gene families of C. hystrix were significantly enriched in "defense response, " and C. hystrix harbored 104 nucleotide-binding site–encoding disease resistance gene analogs. Furthermore, 121 genes were positively selected, and 12 (9.9%) of these were involved in responses to biotic stimuli, which might explain the high disease resistance of C. hystrix . The alignment of whole C. hystrix genome with cucumber genome and self-alignment revealed 45, 417 chromosome-specific sequences evenly distributed on C. hystrix chromosomes. Finally, we developed four cucumber– C. hystrix alien addition lines and identified the exact introgressed chromosome using molecular and cytological methods. The assembled C. hystrix genome can serve as a valuable resource for studies on Cucumis evolution and interspecific introgression breeding of cucumber.